Upaya Penerapan Model Pembelajaran Literasi Awal Untuk Meningkatkan Perkembangan Bahasa Anak Melalui Media Kartu Huruf (Vokal) Pada Kelompok B TK Islam Ridlol Walidain NW Batu Bangka - Baiq Halimatuzzuhrotulaini; Lalu Sunardi; EM. Thonthowi Jauhari; Khairunnisa (Bima Journal of Elementary Education, 2023)
The importance of this research is because language is a basic skill that is very important for children's development and becomes the basis for learning. Thus, the development of an effective early literacy learning model can make a significant contribution in improving the quality of education at an early age. This study aims to test the effectiveness of applying the early literacy learning model using vowel card media in improving children's language development in group B at Ridlol Walidain Islamic Kindergarten NW Batu Bangka. The research method used was classroom action research with a total sample of 20 children. Data analysis was performed using a qualitative descriptive analysis technique. The results showed that the application of the early literacy learning model using vowel card media was effective in improving children's language skills in group B at Ridlol Walidain Islamic Kindergarten NW Batu Bangka. Therefore, it is suggested for educators in kindergarten to consider the use of this media in the development of a better early literacy learning curriculum